IMPLEMENTATION OF STATE SUKUK BASED ON STATE ASSETS - Aziz, Roikhan Mochamad; Yaumi, Anukhrija (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2019)
This study aims to analyze of Sukuk development based on underlying of State Own Property (BMN, Barang Milik Negara) in Indonesia with Islamic Perspective. The data used in this study is the secondary data and the method used Strong Weakness Opportunity Threat Reflexivity Religiosity (SWOTR2) analysis with the help of some literature as sources and interviews conducted during the study. The results of this study indicate that by the end of 2016, the value of Sukuk emission has reached 20,425.4 Billion Rupiah (USD 1,520). With the total of State Budget (APBN) Rp 2,152,695 Billion (USD 159,700), the market share of Sukuk in Indonesia in 2016 reaches 0.95%. To make Sukuk more growing, Indonesia has a new breakthrough by using state assets as an underlying asset in its issuance. However, the use of such underlying assets is only limited to state property (BMN), so it is necessary to extend the state assets used as underlying. Because the wealth of the state is not limited to the existence of a thing in the form of buildings, but also includes all the natural wealth attached to the asset.